Cities, systems and structures: an ontological approach to urban studies - Almeida, R. N. (2019)
Ontological issues lie at the heart of the epistemological, methodological and theoretical discussions over the workings and operations of cities – however, as Castells and Zukin point out, they often find themselves mired in the midst of the praxis of urban studies, for reasons not entirely clear. In this work we attempt to trace a path through the ontology of urban studies, attempting to show the reasons for this apparent omission, as well as showing a possible line of convergence through the lens of systems theory, for a common ontology. We propose a set of analytical classes drawn from the literature, drawn from the need to discuss social phenomena, tracing some of the ontological compromises made in light of such entities. In line with that, we argue there is a need for a transparent phenomenological epistemology, tracing some methodological implications of such processes. We conclude by drawing some scientific and practical implications of these debates for a more general discussion of ontology in urban studies and research.